Numerical studies on reinforced concrete beams subjected to fire load - Balaji, Aneesha; Pallath, Jiji Vijay; Pillai, T.M. Madhavan; Nagarajan, Praveen (Journal of Structural Engineering, 2024)
The current provisions for fire rating of reinforced concrete beam as per Indian Standard code IS 456:2000 is based on tabulated fire rating based on minimum width and cover to reinforcement. The influence of various parameters on the behaviour of reinforced concrete structures subjected to fire is not accounted in the design procedure. This paper presents a three-dimensional nonlinear finite element analysis for evaluating the fire response of reinforced concrete beams using ANSYS. The finite element model accounts for temperature depended thermal properties and a transient time dependent thermal analysis is performed to obtain the temperature distribution in the beam cross-section. The model is validated by comparison with literature on beam tested under fire conditions. The comparison shows that the proposed model is capable of predicting the fire response of reinforced concrete beam with good accuracy. The fire rating of the beam is determined using thermal failure criteria based on critical reinforcement temperature. The tabulated rating provided in IS code is checked by comparing it with the results obtained from numerical analysis. It may be observed that the numerical analysis results are having a lower value than the specified fire rating provided in IS456:2000. Numerical studies are carried out on beam subjected to fire by varying the parameters like type of aggregates, strength of concrete and cover to reinforcement. Through the results of the parametric studies done on beam, it is shown that the parameters have significant influence on fire resistance as per thermal failure criteria. The variation in type of aggregates, increase in strength of concrete and cover to reinforcement increases the fire rating of the beam. It may also note that percentage increase in fire rating decreases with increase in concrete cover. Thus it is improper to excessively increase the cover to reinforcement to improve the fire resistance of beam.